2011
DOI: 10.14742/ajet.905
|View full text |Cite
|
Sign up to set email alerts
|

Technology enabled active learning (TEAL) in introductory physics: Impact on genders and achievement levels

Abstract: This study explored the impact of Technology Enabled Active Learning (TEAL) on students learning general physics, focusing on differences between genders and among various achievement levels. A quasi-experimental investigation was conducted on two semesters of courses offered in 2008. Data sources consisted of pre-tests, posttests, self-report surveys, class observations, and interview data. The test results indicate that the learning gain achieved by the experimental group was 11% higher than that achieved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…4. The students in the study conducted by Shieh et al (2011) reported that a question with a high correct ratio did not necessarily mean that all students comprehended the concept of the question raised. Baird et al (1991) asserted that instant feedback helps students enhance their responsibility and beliefs of learning.…”
Section: Suggestionsmentioning
confidence: 97%
See 1 more Smart Citation
“…4. The students in the study conducted by Shieh et al (2011) reported that a question with a high correct ratio did not necessarily mean that all students comprehended the concept of the question raised. Baird et al (1991) asserted that instant feedback helps students enhance their responsibility and beliefs of learning.…”
Section: Suggestionsmentioning
confidence: 97%
“…The handsets are mapped to each student's ID number or name, which allows the teacher to monitor and track individual students' answers anonymously and statistically. Shieh (2012), in her study investigating the impact of TEAL on teachers and students, reported that implementation of TEAL helped foster the TEAL teacher's confidence in teaching physics courses, and the use of IRSs helped increase class interactivity and the students' study interest (Shieh, Chang, & Liu, 2011). However, whether and how the use of IRSs helped the students enhance their conceptual understanding was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…223-231;Felder and Brent 2009, pp. 122-127;Strachan et al 2010 Technical Authoring 11.1-11.11;Shieh et al 2011Shieh et al , pp. 1082Shieh et al -1099.…”
Section: A Definition Of Active and Passive Learningmentioning
confidence: 99%
“…Such practices are often called Technology Enhanced Learning (TEL). Some studies have shown that the use of TEL technologies has a positive impact on learning engagement and outcomes [2] [3]. However, previous research suggests that there is a disconnection between technologies, research, design and practice [4] [5], and therefore the full potential of IT/IS is not fully utilised [6].Some researchers also argue that the use of technologies does not guarantee the enhancement of learning outcomes [7].…”
Section: Introductionmentioning
confidence: 99%